Dock4 contributes to neuropathic pain by regulating spinal synaptic plasticity in mice - Fu, Qiaochu; Li, Hongyi; Zhu, Zhuanxu; Li, Wencui; Ruan, Zhihua; Chang, Ruijie; Wei, Huixia; Xu, Xueqin; Xu, Xunliang; Wu, Yanqiong (Frontiers in Molecular Neuroscience, 2024)
IntroductionNeuropathic pain (NP) conditions arising from injuries to the nervous system due to trauma, disease, or neurotoxins are chronic, severe, debilitating, and exceedingly difficult to treat. However, the mechanisms of NP are not yet clear. Here we explored the role of Dock4, an atypical Rac1 GEF, in the development of NP.MethodsMechanical allodynia was assessed as paw withdrawal threshold by a dynamic plantar aesthesiometer. Immunofluorescence staining was conducted to investigate the expression and localization of Dock4, Rac1 and GluN2B. Quantitative analysis of Dock4, Rac1 and GluN2B were determined by qRT-PCR and Western blot assay. Spontaneous excitatory and inhibitory postsynaptic currents in spinal cord slices were examined using whole cell patch clam. Dendritic spine remodeling and synaptogenesis were detected in cultured dorsal spinal neurons.Results and discussionWe found that SNL caused markedly mechanical allodynia accompanied by increase of Dock4, GTP-Rac1and GluN2B, which was prevented by knockdown of Dock4. Electrophysiological tests showed that SNL facilitated excitatory synaptic transmission, however, this was also inhibited by Dock RNAi-LV. Moreover, knockdown of Dock4 prevented dendritic growth and synaptogenesis.ConclusionIn summary, our data indicated that Dock4 facilitated excitatory synaptic transmission by promoting the expression of GluN2B at the synaptic site and synaptogenesis, leading to the occurrence of NP.